JURIDICAL REVIEW REGARDING THE CONSTITUTIONALITY OF THE THREE-PERIOD POSITION LIMITS FOR THE PRESIDENT IN THE INDONESIAN LEGAL AND POLITICAL CONTEXT - David Greacy Geovanie (Program Studi Ilmu Hukum, Jurusan Hukum dan Kewarganegaraan, Fakultas Hukum dan Ilmu Sosial, Universitas Pendidikan Ganesha, 2023)
Indonesia as an independent country, of course, has a constitution as a foundation and guideline in carrying out its constitutional system and government. The existence of issues related to the presidential tenure being 3 periods makes this research aim (1) to review the presidential tenure arrangements in terms of the perspective of the currently valid constitution (ius constitutumi), and (2) to find out the idea of ​​construction (ius constituendum ) on the term limits of the president and vice president of the Republic of Indonesia. In this study using the type of normative legal research. The results of this study indicate that (1) the constitutionality of setting limits on the term of office of the president and vice president at present (ius constitutum) which has been regulated in Article 7 of the 1945 Constitution, but the formulation in that article still has several deficiencies so that the idea of ​​legal construction is needed, to be a solution to this deficiency. (2) the term limits for the president and vice president must consider, review and examine the urgency of benefit and justice for the nation and state. Changes related to the president's tenure to 3 periods must also pay attention to other provisions as stipulated in Article 37 of the 1945 Constitution.